The Crucial Role of DNA Methylation and MeCP2 in Neuronal Function - Fasolino, Maria (Genes (Basel), 2017)
A neuron is unique in its ability to dynamically modify its transcriptional output in response to synaptic activity while maintaining a core gene expression program that preserves cellular identity throughout a lifetime that is longer than almost every other cell type in the body. A contributing factor to the immense adaptability of a neuron is its unique epigenetic landscape that elicits locus-specific alterations in chromatin architecture, which in turn influences gene expression. One such epigenetic modification that is sensitive to changes in synaptic activity, as well as essential for maintaining cellular identity, is DNA methylation. The focus of this article is on the importance of DNA methylation in neuronal function, summarizing recent studies on critical players in the establishment of (the “writing”), the modification or erasure of (the “editing”), and the mediation of (the “reading”) DNA methylation in neurodevelopment and neuroplasticity. One “reader” of DNA methylation in particular, methyl-CpG-binding protein 2 (MeCP2), is highlighted, given its undisputed importance in neuronal function.